Healing assessment of fractured femur treated with an intramedullary nail. (May 2021) - Chiu, Wing Kong; Vien, Benjamin Steven; Russ, Matthias; Fitzgerald, Mark
The ability to evaluate the degree of healing of a fractured bone is an integral part of orthopaedic clinical care. The conventional assessment techniques including X-ray and computed tomography are qualitative assessments, where their accuracy is dependent on the surgeon's experience. Although there has been a significant research devoted to accurately define fracture healing, development of more efficient diagnostic tools for an accurate diagnosis of non-unions is still a very subjective area. This article investigates the potential use of the dynamic response to assess the healing of a fractured femur treated with an intramedullary nail. While compared to the conventional method, the dynamic technique is highly advantageous, as it is non-radiative and non-invasive. The experimental work presented utilises an osteotomised composite femur specimen fixated with an intramedullary nail. The test specimen was tightly enclosed by dense and soft modelling clay to simulate the damping effect resulting from mass loading of soft tissues. A long curing adhesive epoxy is applied to the osteotomised region, and the curing of the epoxy is used to simulate the fracture healing process. The results provided evidence indicating that the magnitude and phase of the cross-spectrum, and the coherence function acquired at different healing times from the two-sensor measurement strategy can be used to derive a healing index to quantify the state of healing of the fixated femur. The findings suggest the possible viability of vibrational dynamic technique for healing assessment and, furthermore, its development will yield an assessment technique that complements existing clinical diagnostic tools.